Challenging choices : ideology, consumerism and policy - Clarke, Michael, 1945- (Policy Press, 2010)
This lively and topical book provides a critique of choice in contemporary society and policy. Having choices empowers us, but constant extension of choice overwhelms us. In a concise and readable style, the author considers whether choice enhances or burdens our lives, and questions the blithe assumption that more choice is always for the better.